Diferensiasi Produk Nephelium Lappaceum Linn sebagai Upaya Peningkatan Ekonomi Keluarga di Desa Baletbaru, Kecamatan Sukowono, Kabupaten Jember - Yuliati, Lilis; Aritonang, Gabriel Rianto; Sulaksono, Leonardo Kurniawan; Luqyana, Salsabilla Firyal; Puspitasari, Nazila Dwita Rahma; Musaiyaroh, Ati; Istiyani, Nanik (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
One way to implement the Tridharma of Higher Education is through the Community Service Program (KKN) in the form of student community service. KKN activities are carried out with the aim of developing and building the potential of the village or solving problems in the village. The Research Team consisting of Lecturers collaborated with students from the University of Jember in the University's Village Development Community Service (KKN UMD) in Baletbaru Village, Sukowono District, Jember Regency. Based on identification carried out through direct observation, Baletbaru Village has the potential for village development through the utilization of rambutan commodities that grow abundantly in almost all villages. The Community Service Team found the potential to create home products with high selling power. The method used in village development is the Business Model Canvas. The results of the community service produced products in the form of herbal drinks from rambutan skin with the brand "Anyis", cocktails from rambutan flesh with the brand "Legion", and chips from rambutan wedges with the brand "Bobi". The target of the work program is housewives in Baletbaru Village. The work program activities are expected to be an alternative to improving the family economy in Baletbaru Village.